Money and Capital The Contributions of Capital in the Twenty-First Century to Monetary History and Theory. Issue 1 (March 2015) - Monnet, Éric; Gervais, Darla
Abstract: Like many other historians and economists before him, Thomas Piketty includes money in his definition of capital (wealth). This obliges him to distinguish between real and nominal assets, notably to understand the distributional effect of inflation on capital. This article draws comparisons between this approach and other theories of the difference between money and capital, before going on to show, from a historical point of view, why the role and the share of money within total capital cannot be neglected. Potential substitution effects between monetary and non-monetary assets must to be taken into account in order to understand the historical dynamic of capital and the effects of its taxation.